Limonin Enhances the Antifungal Activity of Eugenol Nanoemulsion against Penicillium Italicum In Vitro and In Vivo Tests - Yi Li; Runan Zhao; Yan Li; Zhiqin Zhou (Microorganisms, 2021)
Penicillium italicum, the cause of citrus blue mold, is a pathogenic fungus that seriously affects the postharvest quality of citrus fruit and causes serious economic loss. In this study, a eugenol nanoemulsion containing limonin, an antimicrobial component from citrus seeds, was prepared using a high-pressure microfluidizer and the antifungal activity of the nanoemulsions against P. italicum was evaluated based on the conidial germination rate, mycelial growth, and scanning electron microscopy analysis. The results showed that the minimum inhibitory concentration and the inhibition rate of limonin-loaded eugenol nanoemulsion was 160 μg/mL and 59.21%, respectively, which was more potent than that of the limonin-free eugenol emulsion. After treatment with the nanoemulsions, the integrity of the P. italicum cell membrane was disrupted, the cell morphology was abnormal, and the leakage of nucleic acid and protein was observed. In addition, the challenge test on citrus fruits revealed that the limonin-loaded eugenol emulsion inhibited citrus infection for longer periods, with an infection rate of 29.2% after 5 days. The current research shows that nanoemulsions containing limonin and eugenol have effective antifungal activity against P. italicum, and may be used as a substitute for inhibiting blue mold in citrus fruits.